Serum concentrations of fibroblast growth factor 19 in patients with obesity and type 2 diabetes mellitus: the influence of acute hyperinsulinemia, very-low calorie diet and PPAR-α agonist treatment - Mráz, M; Lacinová, Z; Kaválková, P; Haluzíková, D; Trachta, P; Drápalová, J; Hanušová, V; Haluzík, M (Physiological research, 2011)
The aim of our study was to measure serum concentrations of fibroblast growth factor 19 (FGF-19) in patients with obesity (OB), obesity and type 2 diabetes mellitus (T2DM) and healthy subjects (C) at baseline and after selected interventions. We measured serum FGF-19 levels and other biochemical and hormonal parameters in 29 OB and 19 T2DM females and 30 sex- and age-matched control subjects. The interventions were acute hyperinsulinemia during isoglycemic-hyperinsulinemic clamp (n=11 for T2DM and 10 for C), very-low calorie diet (VLCD, n=12 for OB) and 3 months treatment with PPAR-alpha agonist fenofibrate (n=11 for T2DM). Baseline serum FGF-19 levels were significantly lower in OB relative to C group (132.1+/-12.7 vs. 202.2+/-16.7 pg/ml, p<0.05), while no significant difference was observed between T2DM and OB or control group. Acute hyperinsulinemia tended to decrease FGF-19 levels in both healthy and T2DM subjects. Three weeks of VLCD in OB group had no significant effect on FGF-19, whereas three months of fenofibrate treatment markedly reduced FGF-19 levels in T2DM patients (194.58+/-26.2 vs. 107.47+/-25.0 pg/ml, p<0.05). We conclude that FGF-19 levels in our study were at least partially dependent upon nutritional status, but were not related to parameters of glucose metabolism or insulin sensitivity.
Keywords: Hyperinsulinism; Obesity; krevní glukóza; fenofibrát; kalorická restrikce; výsledek terapie; Middle Aged; Diabetes Mellitus, Type 2; Adult; diabetes mellitus 2. typu; PPAR alpha; Fenofibrate; Blood Glucose; ženské pohlaví; hyperinzulinismus; Humans; biologické markery; Acute Disease; fibroblastové růstové faktory; lidé středního věku; obezita; Fibroblast Growth Factors; Caloric Restriction; akutní nemoc; dospělí; Biomarkers; inzulinová rezistence; Female; Insulin Resistance; Treatment Outcome; PPAR alfa; lidé